Self-efficacy among middle school students (adolescents) in the city of Khanaqin (Journal of the College of Basic Education, 2022)
The need for progress, creativity and creating important changes in life requires individuals with healthy and effective selves. Self-efficacy is the set of judgments issued by an individual that express beliefs about his ability to perform certain behaviors. The current research is limited to teenage preparatory students in Khanaqin city schools, of both sexes (males-females), and from the academic year (1014-2015), whose number is (200) students. The current research aims to 1- Measuring self-efficacy among middle school students 2- Knowing the differences in self-efficacy according to the gender variable (males-females). The results have shown that the current research sample enjoys self-efficacy. The researcher presented a number of recommendations and proposals.